2021
DOI: 10.1016/j.jcv.2021.104916
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of breast milk antibody titer in the six months following SARS-CoV-2 infection

Abstract: Background : While a growing body of literature describes antibody dynamics in serum, little is known about breast milk antibody titers in the months following SARS-CoV-2 infection. Objectives: We evaluated the dynamics of the humoral immune response to SARS-CoV-2 in two women who were breastfeeding when infected. We assessed paired breast milk and serum samples for six months post-infection for antibodies specific to the SARS-CoV-2 receptor binding domain (RBD) of the spike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Based on systematic review by Low et al [ 10 ] the longest duration of antibody persistence in human milk reported from onset of COVID-19 infection until end of study was 195 days in a single individual [ 13 ]. Duncombe et al reported durable anti-RBD IgA antibodies in breast milk persisting over 6 months [ 14 ] and recent study from Juncker et al reported that IgA antibodies in human milk remain present at least 10 months after PCR confirmed infection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on systematic review by Low et al [ 10 ] the longest duration of antibody persistence in human milk reported from onset of COVID-19 infection until end of study was 195 days in a single individual [ 13 ]. Duncombe et al reported durable anti-RBD IgA antibodies in breast milk persisting over 6 months [ 14 ] and recent study from Juncker et al reported that IgA antibodies in human milk remain present at least 10 months after PCR confirmed infection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding has been shown to play no significant role in the transmission of this virus [ 24 , 25 ]. In fact, many studies have found the breast milk of infected mothers to contain SARS-CoV-2-specific immunoglobulin A (IgA) antibodies up to six months post-infection, strongly suggesting a role for passive viral immunity in the protection of infants [ [26] , [27] , [28] ]. Consistent with these findings, we did not detect any significant differences between children as a function of whether or not they were breastfed.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the role of antibodies found in breast milk from COVID-19 infected mothers on infants has not been specifically studied. In most studies analysing breast milk, reference is made to the fact that future researchers should incorporate not only the presence of SARS-CoV-2 specific antibodies in human milk, but also the maturation, affinity, and functionality of these antibodies [ 84 , 85 ]. IgA antibodies were detected in a study that tested the milk of 2 infected mothers.…”
Section: Discussionmentioning
confidence: 99%
“…IgA antibodies were detected in a study that tested the milk of 2 infected mothers. While this study was not designed to evaluate the level of protection that IgA conferred from mother to infant during prolonged lactation periods, patterns of protection found in other respiratory viruses suggest this confers effective passive immunity, but protection against SARS-CoV-2 infection specifically has yet to be established [ 85 ].…”
Section: Discussionmentioning
confidence: 99%